Engineered biochar: A way forward to environmental remediation. (1st March 2022) - Monga, Divya; Shetti, Nagaraj P.; Basu, Soumen; Raghava Reddy, Kakarla; Badawi, Michael; Bonilla-Petriciolet, Adrián; Aminabhavi, Tejraj M.
Graphical abstract: Highlights: Biochar has unique properties to effectively remove hazardous pollutants. Engineering biochar preparation methods enhance its properties and efficacy. Feedstock composition, carbonization technology and conditions govern biochar properties. It is a low-cost and natural substitute of commercial activated carbons. Abstract: The accelerated urbanization and industrialization worldwide has increased the pollution via toxic chemicals, thus generating environmental hazards to public health and ecosystems. As a consequence, the national authorities and scientists are paying more attention to the development and implementation of viable cost-effective detoxification solutions. Biochar has emerged as a biomass-derived material that can be produced through a variety of feedstocks and carbonization techniques. Distinct characteristics of biochar can be appropriate, cost-effective, and eco-friendly for removing a wide spectrum of inorganic and organic pollutants. This review aims to emphasize the crucial function of biochar-based materials in the abatement of toxic emerging pollutants. It covers the synthesis and applications of engineered biochars by discussing extensive research and knowledge in this area. The relationships of biochar properties with feedstock, synthesis conditions, technologies and modification methods have also been discussed. Biochars with different surface functionalities (e.g., COO −, Fe-O, etc., ) can be obtained by either varying the feedstock material (lignocellulosic or non-lignocellulosic) or by modifying it with different chemicals (e.g., metal ions, rare earth elements, surfactants) including the preparation of composites. The interaction mechanisms between biochar and various pollutants are reviewed and analyzed. The type of interactions (e.g., electrostatic, π-π stacking, hydrogen bonding) depends on the different surface functionalities of biochar. This review also illustrates that biochar and its related composites have shown remarkable properties and versatility for their effective application in adsorption, photocatalysis and oxidation processes in aqueous phase. Finally, prospective research directions and opportunity areas for biochar research are also discussed. The article provides a comprehensive review on the production, modification and environmental application of engineered biochar.